Getting Value for Money in Higher Education - Altbach, Philip; Agarwal, Pawan (International Higher Education, 2013)
India's higher education system, while much criticized, does some things well. It provides impressive rates of access compared to other countries at similar levels of development. India also spends a reasonable proportion of its GDP on education, and pays its academics reasonably well. But it does not get appropriate quality from this level of support.